Social Identity of People With Parkinson’s Disease: An Interpretation of the Disease - Landolfi, Lucia (Italian Sociological Review, 2025)
Considering the body as a communicative entity (Frank, 2022), Parkinson’s disease is a social experience where physicality and identity are interdependent. Although symptoms are individually felt, the discomfort they cause is interpreted and labelled through social interactions. Therefore, a solely clinical perspective limits understanding by neglecting relational and social factors that hinder the fulfilment of people with Parkinson’s disease (Lombi, 2022a). This study assumes that a Parkinson’s diagnosis represents a ‘biographical disruption’ (Bury, 1982) that restructures social relationships. The research question focuses on how diagnosis redefines social identity across the life course. The aim is to analyse the transition from person to person with Parkinson’s disease, highlighting loss of social roles, deviation from collective expectations, and experience of stigma (Goffman, 2003). Through a qualitative approach, interviews were conducted with people with Parkinson’s and informal caregivers. Results show that the diagnosis initiates a negotiation between pre-existing identity and that of a person with Parkinson’s, with the disease closely intertwined with life experiences. Moreover, interpersonal relationships play a crucial role, as informal caregivers and associations provide essential support for daily adaptation. Coping strategies vary according to disease stage and sociocultural context, while digital technologies increasingly emerge as valuable supportive tools. In conclusion, the interpretation of Parkinson’s disease as lived daily by both people with the condition and their informal caregivers highlights how identity transformation profoundly affects everyday life. Recognizing these dynamics is essential to developing inclusive policies and interventions that support autonomy, foster social participation, and improve quality of life.